Correlation Between Patients with Wounds and Isolated Pseudomonas aeruginosa and Staphylococcus aureus at Barau Dikko Teaching Hospital, Kaduna, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
This study was carried out to determine the correlation between patients with wounds and isolated Pseudomonas aeruginosa and Staphylococcus aureus in clinics at Barau Dikko Teaching Hospital, Kaduna, Nigeria. The Socio-demographic, medical and drug histories and characteristics of the wounds from each consented patient were taken using a questionnaire along with sixty samples of the patient’s wound swab samples. Isolation of Pseudomonas aeruginosa and Staphylococcus aureus from the wound swab samples was carried out using standard phenotypic and genotypic procedures. Out of the 60 samples collected, 30 (50.0%) each were from general out-patient and inpatients. The higher percentage 12 (20.0%) and 39 (65.0%) were patients in the age group between 61 and above and male patients respectively. Regarding the patient’s occupations, the higher percentage 20 (33.3%) of the patients were businessmen and women. The patient’s wound location indicated that a higher percentage of 38 (63.3%) wounds were located on the leg. Also, only 13 (21.7%) patients had diabetes and 44 (73.3%) of the wound patients were receiving antimicrobials; the commonest being metronidazole 11 (18.33%), followed by mupirocin/Supirocin 9 (15.6%).  A total of eleven isolates each of Pseudomonas aeruginosa and Staphylococcus aureus were isolated from the sixty wound swab samples of the in-and out-patients. Association between antimicrobial agents use and the organisms showed significant difference (P < 0.05), while the association between sex, diabetes status, duration of the wound and the isolation of Pseudomonas aeruginosa and Staphylococcus aureus from the wound of patients showed no statistically significant difference (P > 0.05).
Keywords: Socio-demographics; Wounds; Pseudomonas aeruginosa; Staphylococcus aureus; Barau Dikko Teaching Hospital Nigeria